Extraction of Organic Compounds From Lacustrine Oil-Prone Shales and the Effect on Nanopore - Cao, Huairen; Zhang, Deping; Wang, Xiaoyu; Fu, Deliang (Frontiers in Earth Science, 2022)
Lacustrine oil-prone shale at the oil-generation stage develops a large number of nanopores; however, the influence of fluid–shale interactions on the nanopores of lacustrine shale is poorly understood. A suite of mature lacustrine shales from the Songliao Basin Qingshankou Formation was performed on sequential organic solvent (petroleum ether and mixture of dichloromethane and methanol) extractions, and nitrogen and carbon dioxide adsorptions, Rock-Eval pyrolysis and field emission scanning electron microscopes (FE-SEM) observation. The sequential extractions show a decrease in total organic matter (TOC) and in the exacted organic matter content of shale, but an increase in the specific area (SBET) and pore volume of the extracted residues. Before and after extractions, the relationships between the extracted amount of OM and SBET, pore volume and their cumulative increments reveal OM as a main factor affecting the development of nanopores in these shales. The reasons are 1) SBET and mesopores are mainly blocked by EOMs in the initial samples, 2) the cumulative increases of SBET and mesopores are dominantly controlled by the extracted amount of hydrocarbons during petroleum ether extraction, and 3) both hydrocarbons and NSOs (resins and asphaltenes) have an influence on the cumulative increases of SBET and mesopores, and kerogen exposed more open porous-organic mesopores after the EOMs in the extracted shales. Here, further work concludes that oils adsorbed on pore surfaces are dominantly distributed on nanopores less than 10 nm, and free oils occur when the threshold of the average pore width in studied shales is over 11.7 nm.